Study on torque and clamping forces of screw‐connected plywood - Cedou Kumpenza (Engineering Reports, 2020)
Abstract In various engineering applications, screws are commonly used to connect wood and engineered wood products to each other. To describe the axial loads which may be transmitted with these components, it is important to quantify the resulting clamping forces in relation to the applied screw torques. In this initial study, birch plywood panels with thicknesses of t = 12, 16, and 20 mm connected with screws (major thread diameter d ≈ 5 mm) are experimentally tested to establish screw driving, tightening and stripping torques. In addition to that, the resulting clamping forces that occur over a time period of 120 hours are monitored and analyzed. A good agreement was found between the established time‐dependent clamping force functions compared to the regression model, which are recommended in the literature.